An Overview on Tablet Coating - Arora, Rimjhim; Rathore, Kamal Singh; Bharakatiya, Meenakshi (Asian Journal of Pharmaceutical Research and Development, 2019)
Pharmaceutical solid dosage forms include tablets, pellets, pills, beads etc. Tablet is most commonly used pharmaceutical dosage form which has ease of administration. Tablets are coated for many reason such as masking odour, taste, colour of the drug, providing physical and chemical protection to drug, protecting drug from the gastric environment.Coating is a process by which a layer of coating material is applied to the surface of a dosage form. Coating may also contain active ingredient. There are various strategies for tablet coating which include sugar coating, film coating, and enteric coating. The amount of coating on the surface of a tablet is critical to the effectiveness of the oral dosage form. Recent trends in tablet coating focuses on overcoming disadvantage of solvent based coating. This review concerns with the coating process, equipments involved, coated tablets evaluation and specialized coating techniques. Key Words: